A guide for English placement examination writing papers - Panjalingam, Nesamalar (IIUM Press, 2016)
A guide for English placement examination writing papers provides students and learners with vital skills which are necessary for success in academic writing. Each chapter has clear conprehensive explanations, notes and exercises in an easy-to-understand format. Useful organisational diagrams are provided for approaching the writing tasks, and model answers offer constructive scaffolding for writing examination candidates.